Masculinity of Madurese Men in the Folk Tale Kè’ Lèsap - Effendy, Moh. Hafid; Hadi, Saiful; Albaburrahim,; Arifin Alatas, Mochamad (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
his study aims to analyze the representation of Madurese masculinity in the folk tale Ke’ Lesap. The focus of the study lies in the values of courage, honor, the symbol of the celurit (traditional sickle), and social responsibility as key pillars of masculinity constructed in the story. This research uses a qualitative approach with descriptive-analytical methods. The primary data consists of the Ke’ Lesap text, collected through document studies, while secondary data is obtained from literature on masculinity and Madurese culture. The analysis technique applies content analysis to identify masculine themes in the story’s quotations, which are then interpreted using the theory of hegemonic masculinity (Connell & Messerschmidt, 2005) and cultural representation theory (Hall, 1997). The results show that masculinity in Ke’ Lesap is embodied through the main character’s courage and willingness to sacrifice for honor, the use of the celurit as a symbol of dignity, and the social role as a protector of community integrity. Masculinity in this tale emphasizes not only individual strength but also moral responsibility toward family and society. These values represent cultural heritage that continues to shape Madurese male identity. shape Madurese male identity.